Research ethics with gender and sexually diverse persons - Henrickson M; Giwa S; Hafford-Letchfield T; Cocker C; Mulé NJ; Schaub J; Baril A (MDPI (Basel, Switzerland))
: Identifying and developing inclusive policy and practice responses to health and social inequities in gender and sexually diverse persons require inclusive research ethics and methods in order to develop sound data. This article articulates 12 ethical principles for researchers undertaking gender and sexually diverse social, health, and related research. We have called these the ‘Montréal Ethical Principles for Inclusive Research.’ While writing from an international social work perspective, our aim is to promote ethical research that benefits people being researched by all disciplines. This paper targets four groups of interest: 1. Cisgender and heterosexual researchers; 2. Researchers who research ‘general’ populations; 3. and sexually diverse researchers; 4. Human ethics committees. This article was stimulated by the 2018 Global Social Work Statement of Ethical Principles, which positions human dignity at its core. It is critically important to understand and account for the intersectionality of gender and sexuality with discourses of race, ethnicity, colonialism, dis/ability, age, etc. Taking this intersectionality into consideration, this article draws on scholarship that underpins ethical principles developed for other minoritized communities, to ensure that research addresses the autonomy of these participants at every stage. Research that positions inclusive research ethics at its foundation can provide a solid basis for policy and practice responses to health and social inequities in gender and sexually diverse persons.
Published source must be acknowledged with citation
Keywords: bisexual; gay; gender diverse; human ethics committees; lesbian; research ethics; transgender; ethical principles